2017
DOI: 10.4049/jimmunol.1601199
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Membrane Vesicles Inhibit T Cell Activation

Abstract: Mycobacterium tuberculosis utilizes multiple mechanisms to evade host immune responses, and inhibition of effector CD4+ T cell responses by M. tuberculosis may contribute to immune evasion. T cell receptor signaling is inhibited by M. tuberculosis cell envelope lipoglycans, such as lipoarabinomannan and lipomannan, but a mechanism for lipoglycans to traffic from M. tuberculosis within infected macrophages to reach T cells is unknown. In these studies, we found that membrane vesicles produced by M. tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 61 publications
1
72
0
2
Order By: Relevance
“…Overall, these proteomic findings combined with our functional studies in human CD4 + T cells and in vivo studies in murine Mtb infection support a model in which ManLAM as Mtb bacterial membrane vesicles can travel beyond the immediate environment of infected cells, that is, the granuloma, to interact with CD4 + T cells and likely others . For CD4 + T cells, this interaction results in inhibition of TCR–CD3 and CD28 signaling with a downstream effect on the Akt‐mTOR signaling pathway, resulting in T‐cell inhibition and anergy.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Overall, these proteomic findings combined with our functional studies in human CD4 + T cells and in vivo studies in murine Mtb infection support a model in which ManLAM as Mtb bacterial membrane vesicles can travel beyond the immediate environment of infected cells, that is, the granuloma, to interact with CD4 + T cells and likely others . For CD4 + T cells, this interaction results in inhibition of TCR–CD3 and CD28 signaling with a downstream effect on the Akt‐mTOR signaling pathway, resulting in T‐cell inhibition and anergy.…”
Section: Discussionsupporting
confidence: 66%
“…We demonstrated direct and indirect inhibition of CD4 + T‐cell activation by different Mtb molecules, including lipoproteins LpqH, LprA, and LprG, and more recently glycolipid mannose‐capped lipoarabinomannan (ManLAM) . ManLAM is abundant in the Mtb cell wall, found in membrane vesicles produced by Mtb, in Mtb granulomas, and most recently in CD4 + T cells from lungs of Mtb‐infected mice . ManLAM interferes with T‐cell receptor (TCR) proximal signaling by downregulating phosphorylation of Lck, CD3ζ, ZAP70, and LAT, and can induce T‐cell anergy, and thus potentially a major modulator of host T cells response to Mtb …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that bacteria-derived EV are released by Mtb -infected mouse macrophages and can act as potent immunomodulators of uninfected cells (5, 6). To determine whether Mtb cells require DLPs to produce EV in macrophages, we compared the abundance of vesicles containing bacterial components released into the culture medium from THP-1 macrophages 24 hours after infection with different Mtb strains: WT, iniA∷hyg , or iniA∷hyg complemented with iniBAC.…”
Section: Resultsmentioning
confidence: 99%
“…Mtb -produced EV ( Mtb -EV) contain many immunologically active lipoproteins and glycolipids (3, 4) and are enriched in polar lipids consistent with a cytoplasmic membrane origin (3). Mtb -EV mediate transfer of bacterial components into immune cells (5, 6) and aid in acquisition of nutritional iron (Fe) by mediating export and uptake of the hydrophobic siderophore, mycobactin (7). Furthermore, Mtb -EV contain protective antigens; immunization with isolated EV elicits a protective immune response against TB in mice that is comparable to BCG vaccination (8).…”
Section: Introductionmentioning
confidence: 99%
“…Whether this mechanism contributes to the inability of T cell responses to eliminate M. tuberculosis in vivo has not been established, but man-LAM and other mycobacterial lipoglycans can be acquired by T cells via bacterial membrane vesicles, and man-LAM can be detected on T cells isolated from lungs of M. tuberculosis-infected mice (Athman et al, 2017). …”
Section: Mechanisms Of T Cell Evasion In Tbmentioning
confidence: 99%